2015
DOI: 10.1051/0004-6361/201425513
|View full text |Cite
|
Sign up to set email alerts
|

Supernova 1987A: neutrino-driven explosions in three dimensions and light curves

Abstract: Context. The well-observed and well-studied type IIP Supernova 1987A (SN 1987A), produced by the explosion of a blue supergiant in the Large Magellanic Cloud, is a touchstone for the evolution of massive stars, the simulation of neutrino-driven explosions, and the modeling of light curves and spectra. Aims. In the framework of the neutrino-driven explosion mechanism, we study the dependence of explosion properties on the structure of different blue supergiant progenitors and compare the corresponding light cur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 122 publications
8
98
0
Order By: Relevance
“…Kifonidis et al (2006) showed that the RT growth rate is considerably boosted by the initial asymmetries that support the onset of neutrino-driven explosions, and Hammer et al (2010) and Wongwathanarat et al (2015) demonstrated, performing 3D simulations of neutrino-driven explosions continuously from core bounce until shock breakout at the stellar surface, that this interaction of initial and secondary instabilities can facilitate the penetration of 56 Ni and 44 Ti with high velocities (up to more than 4000 km s −1 for the fastest clumps) deep into the hydrogen envelope as well as inward mixing of significant amounts of hydrogen to velocities as low as ∼100 km s −1 . For blue supergiant progenitors with compact, small helium cores (∼4-4.5 M ) both effects in combination are efficient enough to produce a good match of the wide, dome-like shape of the light-curve maximum observed for SN 1987A (Utrobin et al, 2015). Wongwathanarat et al (2015), however, found that the interaction of initial and secondary instabilities depends extremely sensitively, and in a subtle way, on the detailed density structure of the progenitor star, which determines the acceleration and deceleration phases of the outgoing shock and therefore the RT growth rates in the unstable layers as well as the time when the reverse shocks collide with the material of the expanding metal core.…”
Section: Explosion Asymmetries and Large-scale Mixingmentioning
confidence: 96%
“…Kifonidis et al (2006) showed that the RT growth rate is considerably boosted by the initial asymmetries that support the onset of neutrino-driven explosions, and Hammer et al (2010) and Wongwathanarat et al (2015) demonstrated, performing 3D simulations of neutrino-driven explosions continuously from core bounce until shock breakout at the stellar surface, that this interaction of initial and secondary instabilities can facilitate the penetration of 56 Ni and 44 Ti with high velocities (up to more than 4000 km s −1 for the fastest clumps) deep into the hydrogen envelope as well as inward mixing of significant amounts of hydrogen to velocities as low as ∼100 km s −1 . For blue supergiant progenitors with compact, small helium cores (∼4-4.5 M ) both effects in combination are efficient enough to produce a good match of the wide, dome-like shape of the light-curve maximum observed for SN 1987A (Utrobin et al, 2015). Wongwathanarat et al (2015), however, found that the interaction of initial and secondary instabilities depends extremely sensitively, and in a subtle way, on the detailed density structure of the progenitor star, which determines the acceleration and deceleration phases of the outgoing shock and therefore the RT growth rates in the unstable layers as well as the time when the reverse shocks collide with the material of the expanding metal core.…”
Section: Explosion Asymmetries and Large-scale Mixingmentioning
confidence: 96%
“…The calibration aims at producing the explosion energy and ejected 56 Ni mass of SN1987A compatible with observations, for which the best values are E exp =(1.50±0.12)×10 51 erg (Utrobin 2005), E exp ∼1.3×10 51 erg (Utrobin & Chugai 2011), and M Ni =0.0723-0.0772 M e (Utrobin et al 2014), but numbers reported by other authors cover a considerable range (see Handy et al 2014 for a compilation). The explosion energy that we accept for an SN1987A model in the calibration process is guided by the ejected 56 Ni mass (which fully accounts for short-time and long-time fallback) and a ratio of E exp to ejecta mass in the ballpark of estimates based on light-curve analyses (see Table 1 for our values).…”
Section: Progenitor Modelsmentioning
confidence: 99%
“…Because of the "gentle" acceleration of the SN shock by the neutrino-driven mechanism (also in 3D simulations;see Utrobin et al 2014), it is difficult to produce this amount of ejected 56 Ni just by shock-induced explosive burning. M Ni 56 in Table 1 mainly measures this component but also contains 56 Ni from proton-rich neutrino-processed ejecta.…”
Section: Progenitor Modelsmentioning
confidence: 99%
“…When the plumes cross the interface between the C-O and He shells, a hydrodynamic process akin to the Rayleigh-Taylor instability stretches them into long, narrow fingers. Some three-dimensional neutrino-driven, core-collapse explosions of Wongwathanarat et al (2013Wongwathanarat et al ( , 2015 and Utrobin et al (2014) It should be emphasized that the production of nickel fingers is sensitive to the precise shock kinematics inside the star; not all stellar models in Wongwathanarat et al (2015) produce fingers. When the forward shock crosses the He-H interface (if the progenitor star has retained its hydrogen envelope), it slows down dramatically, and this excites a reverse shock propagating backward, toward smaller mass coordinates.…”
Section: Abundance Biases and Anomalies In Metal-poor Starsmentioning
confidence: 99%
“…This, of course, has pivotal implications for chemical enrichment. Under which specific conditions are fingers expected is the subject of recent, rapidly developing research (Hammer et al 2010;Wongwathanarat et al 2013Wongwathanarat et al , 2015Utrobin et al 2014).…”
Section: Introductionmentioning
confidence: 99%